Building public sector integrity in Indonesia: the role and challenges of ethical leadership - Jones, Iris van Eden; Lasthuizen, Karin (2018)
Many public sector organisations in developing countries are working ineffectively, which is due considerably to weak standards of governance that result in widespread corruption. Accordingly, this article considers how a public organisation in a corrupt political-economic environment can successfully implement measures to enhance its integrity through an emphasis especially on the role and challenges of ethical leadership. The particular focus is a large state-owned enterprise responsible for the distribution of electricity in Indonesia. The discussion is based on responses to a questionnaire and semi-structured interviews, with the findings confirming that ethical leadership at various levels within and beyond an organisation plays a pivotal role in fostering and maintaining high organisational integrity.
Keywords: Leadership